Komizm w poezji dla dzieci. Jego rola i wartość edukacyjna - Kinga Kuszak (Problemy Wczesnej Edukacji)
The article tackles the subject of comedy in children’s literature. The author begins her reflections with a clarification of the ideas that form the focus of her narration: comedy, humour, and word play, referring to selected works on the subject. Next, adopting her chosen typology of creating comedy in children’s literature, she presents selected examples of literary works which employ the aforementioned linguistic tools to achieve a comedic effect. Contemporary authors’ works are used to illustrate the thesis. The article closes with reflections on the educational role of comedy in children’s literature.